Снижение энергоемкости дезинтеграции горных пород - Vasilyev A. S., Shchukin P. O. (Science and education: future development, 2017)
offered new and patented intellectual property in the design of jaw crusher to reduce the energy intensity of the disintegration of rocks.
Keywords: горные породы; дезинтеграция; rocks; disintegration; jaw crusher; patent; патент щековая дробилка